Overcoming Cache Staleness Issue Using Dynamic Source Routing Protocol (International Journal of Engineering and Computer Science, 2013)
recently, there has been a growing interest in Mobile Ad Hoc Network (MANET). Ad hoc Network becomes popular since it can provide useful personal communication in certain applications such as battlefield, academic, and business without any support where no fixed infrastructure exists. All mobile Nodes communicate with each other direct or through intermediate node using any routing protocol. This paper has focused mainly on Dynamic Source Routing (DSR) protocol regarding route cache. To address the cache staleness issue which leads towards the loss of the packets during delivery of the information in DSR protocol, prior work used adaptive timeout mechanisms. Such mechanisms use heuristics with ad hoc parameters to predict the lifetime of a link or a route. However, heuristics cannot accurately estimate timeouts and as a result of those valid routes will be removed or stale routes will be kept in caches. In this work we will propose proactively disseminating the broken link information to the nodes that have that link in their caches. It is important to inform only the nodes that have cached a broken link to avoid unnecessary overhead. Thus, when a link failure is detected, our goal is to notify all reachable nodes that have cached the link about the link failure which leads towards the minimization of overheads, latency and congestion control of the network